The Students’ Writing Ability to Write Descriptive Text by Using Picture Word Inductive Model (PWIM) - Nurul Hakimah (PGRI Provinsi Jawa Timur, 2022)
The purpose of this research was to enhance students’ descriptive text writing abilities through the implementation of the Picture Word Inductive Model (PWIM) at SMP Negeri 48 Surabaya in the academic year 2020/2021. Classroom Action Research (CAR) was used to study 42 students as the research subjects in class 7-B. The instruments used to collect the data were observation and tests. Pre-test results indicated that students performed below the expected level of success; the mean score was 62.88, the lowest score was 50, and the highest score was 84. Only two students (4.76%) passed the test. Then, in the results of post-test cycle I, the number of students who passed the test based on the success criteria remained at 7 students (16.67%). The mean score was 72.76, with 60 being the lowest and 84 being the highest. However, when compared to the pre-test results, significant improvements in the students’ descriptive text writing ability were observed. In cycle II, post-test results indicated that students’ ability to write descriptive texts had improved slightly. The mean score was 85, with 78 being the lowest and 92 being the highest. 34 students passed the test with an 80.95% passing rate. This research was stopped when it met the success criteria. The result of the t-Test was as follows: Paired Two Samples for Means indicated that the researcher could accept the hypothesis in the event that the post-test mean was greater than the pre-test’s mean. It was concluded that students’ writing abilities improved significantly as a result of the PWIM strategy’s implementation toward students’ writing abilities for descriptive texts.